Analysis of systematic and random coordinate errors of visual landmarks and their effect on positioning algorithm accuracy - Dergachov, Kostiantyn; Hurtovyi, Oleksii; Yaremenko, Anatolii (Національний технічний університет "Харківський політехнічний інститут", 2025)
Visual landmark-based positioning systems are becoming increasingly popular in mobile robotics, autonomous vehicles, and indoor navigation technologies. One of the key factors determining their accuracy is the correctness of landmark coordinates, which in practice can be distorted by both systematic offsets and random noise. This requires a quantitative assessment of the impact of such errors on the operation of positioning algorithms. Subject of research: analysis of the impact of systematic and random errors in determining the coordinates of visual landmarks on the accuracy of positioning algorithms. The research addresses the assessment of sensitivity in different positioning algorithms to offsets and noise in landmark data and to identify critical factors that most affect localization accuracy. Methods applied: simulation modeling with the ability to vary the parameters of systematic and random errors, reproduction of four scenarios (no errors, only bias, only noise, combination). The mean absolute error (MAE) and root mean square deviation (RMSE) were used to assess accuracy. The following results were obtained. Even small errors in the coordinates of landmarks significantly reduce the accuracy of positioning. It was found that systematic errors have a more critical impact on the results compared to random noise. The centroid and weighted centroid methods were the most resistant to errors, while lateration showed high sensitivity to systematic shifts.

Системи позиціонування на основі візуальних орієнтирів набувають все більшого поширення у сфері мобільної робототехніки, автономних транспортних засобів та технологій indoor-навігації. Одним із ключових факторів, що визначає їхню точність, є коректність визначення координат орієнтирів, яка на практиці може спотворюватися як систематичними зміщеннями, так і випадковим шумом. Це потребує кількісної оцінки впливу подібних похибок на роботу алгоритмів позиціонування. Предмет дослідження: аналіз впливу систематичних і випадкових похибок визначення координат візуальних орієнтирів на точність алгоритмів позиціонування. Метою дослідження є оцінка чутливості різних алгоритмів позиціонування до зміщень і шумів у даних орієнтирів та визначення критичних факторів, що найбільше впливають на точність локалізації. Методи, що використовуються: імітаційне моделювання з можливістю варіювати параметри систематичних і випадкових похибок, відтворення чотирьох сценаріїв (без похибок, лише зміщення, лише шум, комбінація). Для оцінки точності застосовано середню абсолютну похибку (MAE) та середньоквадратичне відхилення (RMSE). Були отримані наступні результати навіть невеликі похибки координат орієнтирів суттєво знижують точність позиціонування. Встановлено, що систематичні помилки мають більш критичний вплив на результати порівняно з випадковим шумом. Найбільш стійкими до похибок виявилися методи центроїда та зваженого центроїда, тоді як латерація показала високу чутливість до систематичних зсувів.
Аналіз систематичних та випадкових похибок координат візуальних орієнтирів та їх вплив на точність алгоритму позиціонування
Keywords: systematic errors; random noise; visual landmarks; positioning algorithms; localization accuracy; simulation modeling; Root Mean Square Error; Mean Absolute Error; систематичні помилки; випадковий шум; візуальні орієнтири; алгоритми позиціонування; точність локалізації; імітаційне моделювання; RMSE; MAE